Encapsulated Co3O4/Co on N-PCFs as bifunctional electrocatalysts for rechargeable zinc-air batteries - Ang, Wei Jin (Nanyang Technological University, 2021)
Exploring highly efficient bifunctional oxygen electrocatalysts are important for realising high performance rechargeable zinc-air batteries. The objective of this project was to develop a novel approach for the synthesis of bifunctional electrocatalysts, where Co3O4/Co metal compound are encapsulated in the nitrogen-doped porous carbon fibres (Co3O4/Co on N-PCFs). Next, materials characterization and electrochemical measurements were performed against reference Pt or RuO2 catalysts. Benefiting from its strong synergetic coupling between Co3O4/Co compound and N-doped carbon species, and their hierarchically porous structures, the as-prepared Co3O4/Co@N-PCFs electrocatalyst demonstrate a half-wave potential of 0.838 V for ORR and a kinetic current density (Jk) of 29.322 mA cm−2, which is 4.40 times that of commercial Pt/C (6.657 mA cm−2) at 0.80 V. However, with reasonable OER performance, it could still be improved to achieve more superior electrocatalytic performance for bifunctional electrocatalyst applications. As a demonstration, Co3O4/Co@N-PCFs electrocatalyst is used in the air cathode of a Zn-air battery, which shows superior discharge and charge performance, large power density of 109.3 mW cm−2, small discharge-charge voltage gap of 0.759 V and high voltaic efficiency of 61.3% under ambient conditions. The results of this work showcase the feasibility and designs of highly efficient and advanced bifunctional electrocatalysts to develop rechargeable Zn-air batteries that are likewise, highly efficient, cost-effective and having superior performance. Subsequently, the as-prepared electrocatalysts could still be improved by adding another transition metal or alloy, to achieve better electrocatalytic performance. In addition, utilizing the flexibility of the electrocatalysts would open a novel avenue to design the next generation of high-performance flexible Zn-Air batteries.